Factors influencing job satisfaction / Nur Izzati Maisarah Mohd Bakri - Mohd Bakri, Nur Izzati Maisarah (Faculty of Business and Management, 2018)
Job satisfaction refers to how much an employee feels happy or enjoy with his or her job. It had been the focus of broad study by many researchers in recent years. Latest survey by Job Street had revealed that many employees are dissatisfied with their job. Therefore, this study examine the factors influencing job satisfaction which are working environment and leadership style. Questionnaire had been used as a research instrument to obtain data. A total of 108 questionnaires were distributed to respondents at Urban Transformation Centre (UTC) Melaka and 93 of them were completely returned to the researcher. Therefore, the response rate for this study was accumulated to a percentage of 86%. The sample of study and data was then being analysed using a software known as Statistical Package for Social Science Version 20. The tests involved are Descriptive Analysis, Reliability Analysis, Pearson’s Correlation Analysis and Multiple Regression Analysis. The results of this research indicated that there is significant relationship between working environment and leadership style with job satisfaction and the most influential factor towards job satisfaction is leadership style.